2002
DOI: 10.1124/jpet.301.2.774
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Cellular Expression of Glucocorticoid Receptor and Glucocorticoid Response Element-DNA Binding in Rat Brain during Alcohol Drinking and Withdrawal

Abstract: To define the molecular mechanisms of abnormal hypothalamic pituitary adrenal (HPA) axis during ethanol dependence, we investigated the effect of chronic ethanol treatment (15 days) and its withdrawal (24 h) on the expression of glucocorticoid receptors (GRs) and glucocorticoid response element (GRE)-DNA binding in the rat brain. The effects of chronic mianserin [serotonin (5-HT) 2A/2C antagonist] treatment on these parameters in various brain structures of control diet-fed and ethanolfed rats were also invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 39 publications
1
17
2
Order By: Relevance
“…Moreover, the studies on the time course of the effects of ETH suggest that the effect occurs firstly after 4 h and is stable up to 48 h in undifferentiated U-937 cells. Other studies revealed that ETH also affected GRE binding under in vivo conditions in the rat brain, and that mianserin, another AD, interacts with the effects of ETH on the GR system (Roy et al, 2002). In conjunction with these data, we suggest that the effects of MIRFand also other ADs in our system such as DESIFmay result, to a certain extent, from an interaction with the effects of ETH.…”
Section: Antidepressants Affect Gr Receptors In Human Monocytic Cellssupporting
confidence: 68%
“…Moreover, the studies on the time course of the effects of ETH suggest that the effect occurs firstly after 4 h and is stable up to 48 h in undifferentiated U-937 cells. Other studies revealed that ETH also affected GRE binding under in vivo conditions in the rat brain, and that mianserin, another AD, interacts with the effects of ETH on the GR system (Roy et al, 2002). In conjunction with these data, we suggest that the effects of MIRFand also other ADs in our system such as DESIFmay result, to a certain extent, from an interaction with the effects of ETH.…”
Section: Antidepressants Affect Gr Receptors In Human Monocytic Cellssupporting
confidence: 68%
“…Adult rats fed a chronic alcohol diet (Lieber-deCarli, 15 days) had decreased GRE:DNA binding, as measured by gel electromobility shift assays, that was fully restored after 72 hours of EtOH withdrawal [22]. Further, they showed an EtOH-mediated decrease in GR protein levels in the cortex and hippocampus, which was likely associated with the observed overall decrease in GR:DNA binding in those same regions [22].…”
Section: Discussionmentioning
confidence: 96%
“…The HPA axis exhibits prominent rhythms in hormone secretion and tissue responsiveness (Kalsbeek et al, 2012) and appears to be particularly susceptible to alcohol-induced disruptions (Clarke et al, 2008). Centrally, chronic alcohol can alter levels of corticotropin-releasing hormone (CRH) and vasopressin and also can reduce the expression of glucocorticoid receptors in the paraventricular nucleus of the hypothalamus (Roy et al, 2002;Silva et al, 2002). Peripherally, chronic alcohol has been shown to impair the adrenal sensitivity to adrenocorticotropin and the pituitary responsiveness to CRH (Allen et al, 2011).…”
mentioning
confidence: 98%